Distributed generation a nontechnical guide - Chambers, Ann (PennWell, 2001)
Annotation As the energy market restructures into a significantly more competitive industry, many energy companies are considering distributed generation (DG) as part of a new customer-focused corporate strategy. Chambers, et al cover the technologies associated with DG including diesel engines, gas-fired internal combustion generator sets, fuel cell systems, micro-turbines, and photovoltaic systems in easy-to-understand language. Contents: ? Introduction and background ? Drivers and impacts ? Combustion turbines and micro-turbines ? Fuel cells ? Renewable resources ? Technical application issues ? Project financing and economics ? Utility perspectives and issues ? Conclusions ? Appendices.
Keywords: Distributed generation of electric power.; elektronické knihy; electronic books